Catalogue of Neotropical Plecoptera - Froehlich, Claudio Gilberto (Illiesia, 2010)
The Catalogue of Neotropical Plecoptera lists 508 valid names, of which 32 aredubious. The history of each name is given. The Neotropical Region comprises six families, of which two are endemic to the southern half. The Diamphipnoidae has 3 genera and 6 species, the Eustheniidae, 2 genera and 2 species, the Austroperlidae, 3 genera and 4 species, the Gripopterygidae, 28 genera and 85 species, the Notonemouridae, 4 genera and 18 species and the Perlidae, 10 genera and 393 species, the majority (332 species) in the genus Anacroneuria.
Keywords: entomologija; entomology; Plecoptera; stoneflies; catalogue; Neotropical Region